The Influence of the Work Environment and Work Discipline on the Performance of Employees at the Mukomuko Regional General Hospital, Bengkulu - Agussalim M; Delvianti Delvianti; Anindita Hanung Cahyani (Dinasti International Journal of Management Science, 2023)
This study aims to examine and analyze the influence of the work environment and work discipline on the performance of employees of the Mukomuko Bengkulu General Hospital partially or simultaneously. The data collection method used is a survey technique by distributing questionnaires to respondents. The sample in this study were employees of the Mukomuko Hospital as many as 62 respondents. The sampling technique was Proportionate Stratified Random Sampling. The data analysis technique used is multiple linear regression with the SPSS program. Based on the partial test results, the work environment and work discipline have a positive and significant effect on the performance of the employees of the Mukomuko Bengkulu Hospital. In simultaneous testing, the work environment and work discipline simultaneously have a positive and significant effect on the performance of employees at the Mukomuko Bengkulu Hospital. The coefficient of determination shows that the work environment and work discipline are able to explain the contribution of the influence of the work environment and work discipline to the performance of the employees of the Mukomuko Bengkulu Hospital, which is 69.9%, while the remaining 30.1% is influenced by other variables not included in the study.